Inclusive Food Systems and COVID-19 - Swinnen, Johan (2020)
Johan Swinnen SEMINAR Virtual Event --Discussion of the 2020 Global Food Policy Report Co-Organized by the Ministry of Foreign Affairs, Government of the Netherlands, IFPRI, and Food & Business Knowledge Platform APR 28, 2020 - 10:00 AM TO 11:15 AM EDT